The Role of Women's Digital Literacy in the Effectiveness of Parent Program Policy in Elementary School Learning - Heny Widyawati Saptosari; Eny Haryati; Fedianty Augustinah (International Forum of Researchers and Lecturers, 2026)
This study aims to (1) analyze the role of women's digital literacy in the effectiveness of Parent Program policy implementation in elementary school learning, and (2) formulate a model for strengthening women's digital literacy to enhance the effectiveness of such policy. A mixed methods approach with a sequential explanatory design was employed, involving 248 mothers of elementary school students as survey respondents and 18 key informants for in-depth interviews. Quantitative data were analyzed using multiple linear regression, while qualitative data were analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings indicate that the four pillars of national digital literacy simultaneously explained 62.1% of the variance in Parent Program effectiveness (R² = 0.621), with the largest contribution from digital skills (β = 0.384), followed by digital safety (β = 0.271), digital ethics (β = 0.196), and digital culture (β = 0.142). The study also identified three typologies of mothers based on digital literacy level, namely digital-active, digital-reactive, and digital-dependent. Based on these findings, the model was formulated, consisting of four cyclical components: Maternal Digital Capacity Assessment, Tiered Mentoring, Inclusive Communication Governance, and Participatory Evaluation. This study contributes to the development of gender-sensitive and digitalization-adaptive education policy implementation studies in public administration.